- PENGARUH PELAYANAN FASILITAS RUANG TUNGGU KEBERANGKATAN INTERNASIONAL TERHADAP KEPUASAN PENUMPANG BANDAR UDARA INTERNASIONAL YOGYAKARTA: PENGARUH PELAYANAN FASILITAS RUANG TUNGGU KEBERANGKATAN INTERNASIONAL TERHADAP KEPUASAN PENUMPANG BANDAR UDARA INTERNASIONAL YOGYAKARTA - Ardiansyah, Muhammad Zaky; Soebagio, Agoes; Arnas, Yenni (FTK UNSURYA, 2025)
This research is motivated by the condition of the Yogyakarta International Airport international departure waiting room service facilities which is not fully operating, in terms of the use of the waiting room area to the unavailability of important facilities. The main objective of this study is to determine the impact of facilities service that provide comfort and added value to the level of passenger satisfaction. The research was conducted with a quantitative approach using multiple regression methods supported by qualitative secondary data in the form of observations, interviews, and document studies. The results of multiple regression analysis show that facilities that provide comfort have a coefficient value of 0.118 and value-added facilities have a coefficient value of 0.461 which indicates that there is a significant impact on passenger satisfaction, both partially and simultaneously. Facilities that provide comfort have a moderate correlation value of 0.514 and facilities that provide added-value show a very strong correlation of 0.805 to passenger satisfaction. The percentage of variation in passenger satisfaction variables that can be explained by the two independent variables is 68.7%. With these results, all alternative hypotheses are accepted and the null hypothesis is rejected. In the secondary data, a more in-depth passenger perspective is generated which shows that there is still dissatisfaction characterized by a gap between user expectations in waiting room facility services and the experience felt directly by passengers. The same pattern of complaints between observations, interviews, and document studies reinforces that issues related to facilities are real problems that need to be addressed seriously by airport managers.